2020
DOI: 10.3390/ijms21031102
|View full text |Cite
|
Sign up to set email alerts
|

Targeting MAPK Signaling in Cancer: Mechanisms of Drug Resistance and Sensitivity

Abstract: Mitogen-activated protein kinase (MAPK) pathways represent ubiquitous signal transduction pathways that regulate all aspects of life and are frequently altered in disease. Here, we focus on the role of MAPK pathways in modulating drug sensitivity and resistance in cancer. We briefly discuss new findings in the extracellular signaling-regulated kinase (ERK) pathway, but mainly focus on the mechanisms how stress activated MAPK pathways, such as p38 MAPK and the Jun N-terminal kinases (JNK), impact the response o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
338
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 486 publications
(393 citation statements)
references
References 205 publications
7
338
1
1
Order By: Relevance
“…The three primary components of MAPKs are p38, JNK, and ERK; ERK is primarily involved in survival, whereas p38 and JNK are responsive to stress conditions, including the apoptotic phenotype [ 21 ]. In cancer cells, however, MAPK signaling cascades are dysregulated, owing to genetic mutations or environmental stimuli; hence, numerous studies have focused on developing therapeutic agents to restore the balance of MAPK function [ 22 ]. In this study, p38, though not JNK and ERK, was phosphorylated during CT-mediated HL-60 apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The three primary components of MAPKs are p38, JNK, and ERK; ERK is primarily involved in survival, whereas p38 and JNK are responsive to stress conditions, including the apoptotic phenotype [ 21 ]. In cancer cells, however, MAPK signaling cascades are dysregulated, owing to genetic mutations or environmental stimuli; hence, numerous studies have focused on developing therapeutic agents to restore the balance of MAPK function [ 22 ]. In this study, p38, though not JNK and ERK, was phosphorylated during CT-mediated HL-60 apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…medical therapies in tumor: for example, drugs targeting MAPK signaling in cancer (Lee et al, 2020), may also be effective in keloid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we identi ed that the GRP75/HMGA1 axis plays an oncogenic role by activating JNK/c-JUN signaling. Various ndings have reported that activation of the JNK/c-JUN signaling pathway is closely correlated with cancer progression, including recurrence [37][38][39]. For instance, Jorgense et al…”
Section: Discussionmentioning
confidence: 99%